«Physics-1» virtual computer laboratory - Daineko, Y.A.; Dmitriyev, V.G.; Chaiko, Y.V.; Ipalakova, M.T. (Recent Contributions to Physics, 2012)
The main idea of this article is using the multimedia technologies in the education process. The essential aspects of the structuring and presentation of the theoretical and experimental materials within the virtual computer laboratory are presented. The virtual computer laboratory developed is based on the Physics subject. The laboratory contains four laboratory sessions in English language «Study of kinematics and dynamics on the Atwood’s machine», «Study of momentum of inertia with Maxwell’s pendulum», «Definition of the rate of adiabat for air using the Kleman-Dezorm method», «Measurement of the horizontal component of the Earth magnetic induction’s horizontal project».